The upper room - Watson, John, 1850-1907. (New York : Dodd, Mead & Co., 1895)
Lessons from the closing scences of the life of Christ.
The goodman of the house -- The guest-chamber of the soul -- The Twelve -- The shadow of the Cross -- A last wish -- The bequest of Jesus -- The Lord's tryste.
Publisher's advertisement on p. [4] of first sequence of pagination: "Other volumes in this series [i.e. Little books on religion]".
Keywords: Jesus Christ -- Devotional literature; Lord's Supper